Political Thought of Russia’s Allies in Poland in 1920: An Intellectual History of B.V. Savinkov Group - F. A. Popov (Научный диалог, 2025)
This article reconstructs the political thought of the Russian anti-Bolshevik emigration in Poland during the Polish-Soviet War and the subsequent peace negotiations. The primary sources include materials from the Warsaw newspaper “Svoboda,” published by the Russian Political Committee (RPK) led by B.V. Savinkov. It emphasizes that, operating on foreign soil, émigrés laid the ideological groundwork for Russian-Polish cooperation. The article notes that Polish authorities harbored distrust towards the White movement, perceiving it as a potentially hostile force against Poland. It demonstrates that the RPK sought to dispel these suspicions by openly declaring a pro-Polish stance, which, in turn, provoked irritation among the right wing of Russian society (monarchists and supporters of “United and Indivisible Russia”). The author concludes that B.V. Savinkov, during the Civil War years, adopted a nationalist discourse, reflecting the influence of Józef Piłsudski — a socialist, revolutionary, and nationalist. The question of an independent Poland as a source of inspiration for democratic émigrés, who hoped for a similar awakening of Russian national consciousness, is also raised. The relevance of this study lies in the necessity to explore the Civil War within the context of intellectual history.